Should common law marriage be abolished? - Shoshana Grossbard (IZA World of Labor, 2016)
In addition to regular marriage, Australia, Brazil, and 11 US states recognize common law (or de facto) marriage, which allows one or both cohabiting partners to claim, under certain conditions, that an informal union is a marriage. France and some other countries also have several types of marriage and civil union contracts. The policy issue is whether to abolish common law marriage, as it appears to discourage couple formation and female labor supply. A single conceptual framework can explain how outcomes are affected by the choice between regular and common law marriage, and between various marriage and civil union contracts.
Keywords: J10; J12; J13; J16; J22; K36; 330; common law marriage; couple formation; marriage; labor supply; fertility; civil unions